Bout time for krill: contrasting Adélie penguin foraging behaviour during years of high and low krill availability - Riaz, Javed; Machado-Gaye, Ana Laura; Chimienti, Marianna; Kato, Akiko; Ropert-Coudert, Yan; Alegría, Nicolás; Barbosa, Andrés; Soutullo, Alvaro (Animal Behaviour, 2025)
Understanding how marine predators structure and adjust their foraging in response to prey field characteristics is a longstanding objective in marine ecology. This is particularly challenging in Southern Ocean ecosystems, where logistical and financial constraints hinder assessment of predator foraging and prey field information at relevant spatial and temporal scales. Here, we examine how Adélie penguins, Pygoscelis adeliae, a key Southern Ocean indicator species, perform and organize their foraging behaviour during two contrasting years of krill (Euphausia superba) abundance. Using multiyear krill acoustic data from King George Island in the West Antarctic Peninsula (WAP), we assess broad seasonal conditions in krill availability. We also analyse a suite of penguin biologging data (spatial location, dive and accelerometry-derived activities) during the same period to identify broad behavioural differences in their bout-diving activity, a classical measure of the temporal organization of foraging in diving predators. During years of high krill abundance and availability, penguins performed shorter dive bouts (consisting of shallower and shorter-duration dives), which were more concentrated in time and space. Despite these differences in bout structure, prey capture attempts occurred at the same rate within bouts. These findings challenge traditional interpretations assuming that increased bout durations (and related proxies of prey capture effort) signal increased krill patch abundance and profitability. Although additional data are required to understand the full scope of penguin bout diving and krill prey field associations, our work improves understanding of penguin behavioural variation and provides insights into how foraging behaviours could potentially be used to interpret krill availability at predator- and management-relevant scales.
Article number: 123260
Keywords: Sørishavet; ekkolodd; krill; marin biologi; marin økologi; marine økosystemer; matauk; pingviner; plankton

A new dynamic distribution model for Antarctic krill reveals interactions with their environment, predators, and the commercial fishery in the south Scotia Sea region - Freer, Jennifer J.; Warwick-Evans, Victoria; Skaret, Georg; Krafft, Bjørn A.; Fielding, Sophie; Trathan, Philip N. (Limnology and Oceanography, 2025)
The management strategy for the Antarctic krill (Euphausia superba) fishery is being revised. A key aim is to spatially and temporally allocate catches in a manner that minimizes impacts to both the krill stock and dependent predators. This process requires spatial information on the distribution and abundance of krill, yet gaps exist for an important fishing area surrounding the South Orkney Islands in the south Scotia Sea. To fill this need, we create a dynamic distribution model for krill in this region. We used data from a spatially and temporally consistent acoustic survey (2011-2020) and year-specific environmental covariates within a two-part hurdle model. The model successfully captured observed spatial and temporal patterns in krill density. The covariates found to be most important included distance from shelf break, distance from summer sea ice extent, and salinity. The northern and eastern shelf edges of the South Orkney Islands were areas of consistently high krill density and displayed strong spatial overlap between intense fishing activity and foraging chinstrap penguins. High mean krill density was also linked to oceanographic features located within the Weddell Sea. Our data suggest that years in which these features were closer to the South Orkney shelf were also years of positive Southern Annular Mode and higher observed krill densities. Our findings highlight existing fishery?predator?prey overlap in the region and support the hypothesis that Weddell Sea oceanography may play a role in transporting krill into this region. These results will feed into the next phase of krill fisheries management assessment.
Publisher: John Wiley & Sons, Ltd
Keywords: Scotiahavet; Sør-Orknøyene; Sørishavet; Weddellhavet; ekkolodd; fiskerier; krill; oseanografi; plankton

Automated krill body length estimation based on stereo camera images - Svantemann, Mette M; Krafft, Bjørn A; Thompson, Fletcher F; Zhang, Guosong; Krag, Ludvig A (ICES Journal of Marine Science, 2025)
The fishery for Antarctic krill (Euphausia superba) is the largest by tonnage in the Southern Ocean, and understanding its population dynamics is essential for the sustainable management of this fishery. The standard method for calculating Antarctic krill biomass relies on hydroacoustic survey data and incorporates krill body length data collected concurrently. Traditional scientific acoustic surveys involve manually measuring the body lengths of individual krill caught using fine- meshed nets or trawls along acoustic transects. This work is resource-demanding and could represent a source of human error. To address these challenges, we develop and test an alternative, more automated method for estimating krill body length data by employing an in-trawl stereo camera system. This system collects images that are automatically processed by a custom-trained machine learning model. The results from the machine learning model are then compared to manually measured krill subsampled from the total catch of the corresponding trawl hauls. We demonstrated the ability to extract body lengths from underwater images. However, our results highlighted uncertainties, which we propose addressing by incorporating more advanced camera technology and optimizing the observation section of the small-meshed two-layer krill trawl.
Article number: fsaf058
Keywords: Sørishavet; ekkolodd; fiskerier; fiskeriforvaltning; krill; marin biologi; plankton

Enhanced basal melting in winter and spring: seasonal ice–ocean interactions at the Ekström Ice Shelf, East Antarctica - Zeising, O.; Hattermann, T.; Kaleschke, L.; Berger, S.; Boebel, O.; Drews, R.; Ershadi, M. R.; Fromm, T.; Pattyn, F.; Steinhage, D.; Eisen, O. (The Cryosphere, 2025)
Basal melting of Antarctic ice shelves significantly contributes to ice sheet mass loss, with distinct regional disparities in melt rates driven by ocean properties. In Dronning Maud Land (DML), East Antarctica, cold water predominantly fills the ice shelf cavities, resulting in generally low annual melt rates. In this study, we present a 4-year record of basal melt rates at the Ekström Ice Shelf, measured using an autonomous phase-sensitive radio-echo sounder (ApRES). Observations reveal a low mean annual melt rate of 0.44 m a−1, with a seasonal variability. Enhanced melting occurs in winter and spring, peaking at over 1 m a−1, while rates are decreased in summer and autumn. We hypothesise that the dense water formed during sea-ice formation erodes the water column stratification during late winter and spring, leading to an increase in the buoyancy of the ice shelf water plume. An idealised plume model supports this hypothesis, indicating that the plume velocity is the primary driver of seasonal basal melt rate variability, while changes in ambient water temperature play a secondary role in the range of oceanographic conditions that are observed below the Ekström Ice Shelf. These findings offer new insights into the dynamics of ice–ocean interactions in East Antarctica, emphasising the need for further observations to refine our understanding of ocean variability within ice shelf cavities and improve assessments of ice shelf mass balance.
Publisher: Copernicus Publications
Keywords: Dronning Maud Land; ekkolodd; glasiologi; havis; isshelf; oseanografi; sjøis